2003
DOI: 10.1177/107424840300800302
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic Reversion of Persistent Atrial Fibrillation with Amiodarone Predicts Long-Term Sinus Rhythm Maintenance

Abstract: In patients with persistent atrial fibrillation, long-term preservation of sinus rhythm under chronic amiodarone treatment may be anticipated when the arrhythmia lasts 12 months or less and/or its reversion is obtained pharmacologically. We may confidently assume that these two factors have a beneficial additive influence on the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…There have been no consistent reports of sex-specific differences in the type of antiarrhythmic used in observational studies 31,32 . Likewise, no sex-specific differences in likelihood of sinus rhythm have been shown with the use of antiarrhythmics 36 . Some studies have reported that rhythm-control medications increased the risk of torsades de pointes 37,38 and sick sinus syndrome in women compared with men 39 .…”
Section: Rate and Rhythm Controlmentioning
confidence: 99%
“…There have been no consistent reports of sex-specific differences in the type of antiarrhythmic used in observational studies 31,32 . Likewise, no sex-specific differences in likelihood of sinus rhythm have been shown with the use of antiarrhythmics 36 . Some studies have reported that rhythm-control medications increased the risk of torsades de pointes 37,38 and sick sinus syndrome in women compared with men 39 .…”
Section: Rate and Rhythm Controlmentioning
confidence: 99%
“…Although therapeutic antiarrhythmic drug levels immediately after cardioversion can prevent immediate recurrences of AF, pretreatment does not routinely used in common clinical practice. Nonetheless, some observational data sets are available for patients pretreated with amiodarone 13 and dofetilide 14 : Galperín et al 13 analysed the role of different parameters that determine long-term SR maintenance in patients with persistent AF who are treated with amiodarone. They enrolled 141 anticoagulated patients with persistent AF who were pretreated for 4 weeks with oral amiodarone.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse pharmacologic strategies directed toward long-term preservation of normal SR after reversion of persistent AF have been proposed, with modest antiarrhythmic efficacy and the incidence of limiting and even harmful adverse effects [17,18]. Long-term amiodarone treatment is among the most effective treatments for promoting normal SR maintenance in patients with persistent AF [4][5][6][7]. However, the untoward side effects of the drug increase along with the duration of administration.…”
Section: Discussionmentioning
confidence: 99%
“…This can be prevented in a substantial percentage of patients by using long-term amiodarone therapy [4][5][6]. However, amiodarone treatment is associated with significant side effects, including hyperthyroidism or hypothyroidism, pulmonary and hepatic toxicity, and neurological symptoms, which may preclude the benefits of this approach [7,8].…”
Section: Introductionmentioning
confidence: 99%